1996
DOI: 10.1097/00005392-199601000-00091
|View full text |Cite
|
Sign up to set email alerts
|

Combined Endoscopic Closure of Rectourethral Fistula

Abstract: Any open procedure to correct a rectourethral fistula is considered major surgery. Therefore, the minimally invasive approach described should be attempted first in patients with a small rectourethral fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 6 publications
1
14
0
1
Order By: Relevance
“…5,6 As with any rare or complicated surgical problem, many types of repairs have been described, including transperineal, transsphincteric, and transanal flap repairs; gracilis muscle interposition; transabdominal repair; and transanal endoscopic repair. [7][8][9][10][11][12] These repairs are supported by data from many studies. [13][14][15][16][17][18] Other studies report modified repairs including a combination of the transsphincteric approach with advancement flap closure, combination rectal advancement flap and gracilis muscle interposition, transsphincteric approach without diversion, and perineal approach with gracilis muscle interposition.…”
supporting
confidence: 56%
“…5,6 As with any rare or complicated surgical problem, many types of repairs have been described, including transperineal, transsphincteric, and transanal flap repairs; gracilis muscle interposition; transabdominal repair; and transanal endoscopic repair. [7][8][9][10][11][12] These repairs are supported by data from many studies. [13][14][15][16][17][18] Other studies report modified repairs including a combination of the transsphincteric approach with advancement flap closure, combination rectal advancement flap and gracilis muscle interposition, transsphincteric approach without diversion, and perineal approach with gracilis muscle interposition.…”
supporting
confidence: 56%
“…Wilbert et al [11] reported 2 cases with a rectourethral fistula which was successfully corrected by TEM. The most important advantage in using TEM, we think, is the fact that visualization of the fistula is excellent without any incision in healthy tissue such as in York-Mason procedure or perineal approach.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent RUF may require patients to be subjected to permanent urinary and fecal diversion [8]. Hence, many different surgical options for fistula repair have been reported including multiple approaches, such as abdominal, vesical, sagittal, and perineal [9][10][11][12][13]. Castillo et al for instance presented a anterior transanal, transsphincteric sagittal approach for fistula repair after laparoscopic radical prostatectomy.…”
Section: Discussionmentioning
confidence: 99%